EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN GROUP INVESTIGATION UNTUK MENINGKATKAN KOMUNIKASI MATEMATIS SISWA DI KELAS X SMA NEGERI 1 PADANG BOLAK - Sartika Siagian (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
This study aims to describe the effectiveness of using group investigation learning model to increase students’ mathematical communication at the tenth grade students at SMA Negeri 1 Padang Bolak. The research was conducted by using quasi experimental method (pretest post test one group design) with 36 students as the sample and they were taken by using cluster random sampling technique from 139 students. Test and observation were used in collecting the data. Based on descriptive analysis, it could be found (a) the average of using group investigation learning model was 3.67 (very good category) and b) the average of students’ mathematical communication ability before using group investigation learning model was 53.56 (fair category) and after using group investigation learning model was 78.72 (good category). Furthermore, based on inferential statistic by using paired sample ttest and helping SPSS version 16, the result showed the significant value was less than 0.05 (0.000<0.05). It means, the used group investigation learning model is effective to increase students’ mathematical communication at the tenth grade students at SMA Negeri 1 Padang Bolak.